2023
DOI: 10.1097/ms9.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine in the management of COVID-19 adult patients admitted to ICU: a prospective observational cohort study

Abstract: Background: COVID-19 infection is associated with high mortality, and despite extensive studying the scientific society is still working to find a definitive treatment. Some experts postulated a beneficial role of Deferoxamine. Aim: The aim of this study was to compare the outcomes of COVID-19 adult patients admitted to the ICU who received deferoxamine to those who received standard of care. Methods: Prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that both iron chelators and lipophilic antioxidants could prevent the progression of PD [ 107 ]. Furthermore, deferoxamine lowers the amounts of IL-6, a major inflammatory cytokine generated during COVID-19 [ 108 ], suggesting that deferoxamine may be used as a medication to treat COVID-19-induced PD. Nevertheless, no study has yet evaluated the effectiveness of lipophilic antioxidants in the COVID-19 therapy process.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that both iron chelators and lipophilic antioxidants could prevent the progression of PD [ 107 ]. Furthermore, deferoxamine lowers the amounts of IL-6, a major inflammatory cytokine generated during COVID-19 [ 108 ], suggesting that deferoxamine may be used as a medication to treat COVID-19-induced PD. Nevertheless, no study has yet evaluated the effectiveness of lipophilic antioxidants in the COVID-19 therapy process.…”
Section: Discussionmentioning
confidence: 99%